New-onset and relapsed liver diseases following COVID-19 vaccination: a systematic review - Alhumaid, Saad; Al Mutair, Abbas; Rabaan, Ali A; AlShakhs, Fatemah M; Choudhary, Om Prakash; Yong, Shin Jie *; Nainu, Firzan; Khan, Amjad; Muhammad, Javed; Alhelal, Fadil; Al Khamees, Mohammed Hussain; Alsouaib, Hussian Ahmed; et al. (BMC, 2022)
Background: Liver diseases post-COVID-19 vaccination is extremely rare but can occur. A growing body of evidence has indicated that portal vein thrombosis, autoimmune hepatitis, raised liver enzymes and liver injuries, etc., may be potential consequence of COVID-19 vaccines.